Implementation of Discovery Learning Method in Islamic Religious Education Learning: A Qualitative Study in Madrasah - Dewi Anisatur Rohmah; Aminatus Zahroh (Al-Qalam Institue, 2026)
This study aims to analyze the implementation of Discovery Learning in Islamic Religious Education (PAI) learning and examine its contribution to improving student engagement, understanding, and character development. This research employed a qualitative approach with a descriptive design. Data were collected through observation, semi-structured interviews, and documentation, while data analysis involved data condensation, data display, and conclusion verification. The findings reveal that Discovery Learning was implemented through systematic stages, including stimulation, problem identification, data collection, data processing, verification, and generalization. The implementation encouraged students to actively participate, develop independent learning skills, improve conceptual understanding, and strengthen Islamic character values such as responsibility, cooperation, confidence, and discipline. The study also identifies several challenges, including limited learning time, differences in student abilities, and the need for continuous teacher development. The implication of this research highlights that Discovery Learning can serve as an effective alternative strategy for creating meaningful, student-centered, and contextual PAI learning. This study contributes to strengthening innovative practices in Islamic education by demonstrating the integration of cognitive development, active learning experiences, and character formation.